2023
DOI: 10.3390/cells12182228
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease Is Associated with a Decreased Catalase (CAT) Level, CT Genotypes and the T Allele of the -262 C/T CAT Polymorphism

Marcin Kosmalski,
Izabela Szymczak-Pajor,
Józef Drzewoski
et al.

Abstract: Background: It is well known that oxidative stress plays an important role in the development of non-alcoholic fatty liver disease (NAFLD). It has been suggested that an insufficient antioxidant defense system composed of antioxidant enzymes, including catalase (CAT) and nonenzymatic molecules, is a key factor triggering oxidative damage in the progression of liver disease. Therefore, the aim of our study was to assess whether the level of CAT and -262 C/T polymorphism in the promoter of CAT (rs1001179) are as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…CAT is an important antioxidant enzyme in the body that reduces oxidative stress in tissues by breaking down hydrogen peroxide into water and oxygen. 16 The effects of L. plantarum CCFM8661 on CAT activity in the liver and kidney tissues of mice are shown in Fig. 3b and 4b.…”
Section: Resultsmentioning
confidence: 97%
“…CAT is an important antioxidant enzyme in the body that reduces oxidative stress in tissues by breaking down hydrogen peroxide into water and oxygen. 16 The effects of L. plantarum CCFM8661 on CAT activity in the liver and kidney tissues of mice are shown in Fig. 3b and 4b.…”
Section: Resultsmentioning
confidence: 97%
“…However, preclinical studies concerning catalase favor its role in addition to preclinical studies. Recent in vivo observations have shown that decreased catalase levels, leading to an insufficient antioxidant defense system, are a characteristic of 139 NAFLD patients [ 154 ]. In addition, methyl donors, such as S-adenosylmethionine (SAMe) and betaine, may act via the attenuation of alcohol-induced oxidative stress in male C57BL/6 J mice [ 155 ].…”
Section: Other Common Mechanismsmentioning
confidence: 99%